Adverse drug reaction (ADR) reporting in India: a long way to go - Patil, Anant D. (International Journal of Basic & Clinical Pharmacology, 2017)
New drugs are regularly introduced for treatment, diagnosis or prevention of diseases. Adverse drug reactions (ADR) can be seen in clinical practice with both new as well as marketed medicines. Spontaneous reporting of ADR is commonly practiced method for monitoring of ADR. Healthcare practitioners have an important role in pharmacovigilance and ADR reporting. Many studies have been conducted to understand the knowledge, attitude and practice of ADR reporting among healthcare practitioners in India. The population surveyed in these studied ranged between 90-1200. One large study4 included population of 1200 physicians across India out of which 1000 were contacted for study participation.